Assessment of soil microbial properties in some regions affected by climate change - Mohammed Khalid Al-Atrash; Fatima Amer Abd Algabar; Lamiaa Saoud Abbod (Caspian Journal of Environmental Sciences)
Climate change and human activity may have profound impacts on ecosystems sustainability and soil degradation. Within this context, soil microbial properties represented by microbial biomass and enzymatic activities have been used as soil quality assessing bioindicators. Twenty soil samples were collected from five unmanaged lands with native vegetation cover in areas around Baghdad, Iraq. The microbial biomass carbon (MBC) and microbial biomass nitrogen (MBN) were evaluated by the chloroform fumigation - extraction method. The soil enzymes activity was estimated by fluorescence enzyme assays. The current study showed a significant decrease in the activity of soil microbial communities in this region in response to climate changes that affected physicochemical soil properties. Neither pH nor electrical conductivity was significantly correlated with phosphatase activity. Electrical conductivity was negatively correlated with microbial biomass content and nitrifying enzymes activity. Soil moisture was strongly correlated with microbial biomass and enzymatic activity. Furthermore, microbial biomass carbon and nitrogen were significantly lower at all study sites. Our data indicate that the soil state was stressful, specific, and less efficient in supporting soil microbial activity. Consequently, lands reclamation would contribute to reducing soil degradation. This is the first analysis of bioindicator measurements of soil in a hot and dry ecosystem in the Middle East.